Socioeconomic status and social capital as predictors of happiness : evidence and gender differences - Adekunle Adedeji and Tosin Tunrayo Olonisakin and Johanna Buchcik and Erhabor S. Idemudia (Humanities and Social Sciences Communications, 2023)
Understanding socioeconomic status (SES) and social capital as predictors of life outcomes has remained central to humanitarian, health and social research. This current study explores how socioeconomic status and social capital (community solidarity, locus of control and generalised trust) predict happiness among a sample of South African adults. Possible gender differences were also considered. Cross-sectional data from (n = 1049) South Africans on SES, social capital, happiness and sociodemographic characteristics were collected using an online questionnaire between January 2021 and September 2021. A correlation matrix was calculated to explore bivariate associations between the variables. Hierarchical regression analysis was conducted to examine the predictive influence of SES and social capital indices on happiness and the gender differential in these relationships. SES and all social capital variables were significantly correlated with happiness. The model, including SES and social capital, accounted for 25% of the variance in happiness. Gender differences were found regarding the relationship between SES and all social capital variables (except locus of control) and happiness. The results confirm that efforts to facilitate individual social capital correspond to greater happiness among South Africans. Furthermore, it highlights the need for further empirical exploration of social predictors of life outcomes. The current analysis provides a framework for developing and implementing policies that promote happiness and other life outcomes.